The role of vitamin D in ocular diseases - a literature review - Aleksandra Partyka; Martyna Dyrek; Cezary Kopczyński; Urszula Kopczyńska; Kinga Gurdak; Martyna Dydyk; Piotr Malinowski; Piotr Sikorski; Ewa Błaszczak; Jakub Wójcik (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Vitamin D is a steroid hormone that can modulate immune and inflammatory responses. Recent investigations have shed light on its potential role in the pathogenesis of many diseases affecting the eyes. Aim of the study: This paper aims to provide a comprehensive review of the existing findings on the relationship between vitamin D and ocular diseases. The intention is to present new perspectives that will contribute to a better understanding of the complicated nature of this aspect. Material and methods: This review included relevant papers from PubMed database using specified keywords. Analysis of the literature: The role of vitamin D in ocular and visual health has been observed in many studies. A deficiency of vitamin D may play a significant role in the development of many ocular diseases such as dry eye disease, myopia, diabetic retinopathy, keratoconus, and thyroid eye disease. Conclusions: Adequate vitamin D levels are significant for maintaining ocular health. Recognition of the pivotal role of vitamin D in ocular diseases opens new possibilities for potential therapeutic interventions. Ongoing research is needed to further investigate that aspect. Supplementation of vitamin D may prevent or modulate many diseases affecting the eyes.